Board Structure in the Control of Real Earnings Management: Does Profitability Play a Role? Evidence from Indonesia’s LQ45 - Putri, Sarah Widyana; Valdiansyah, Riyan Harbi; Firmansyah, Amrie (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2024)
This study analysed the role of the audit committee as a moderating variable on the relationship between board structure and real earnings management, with profitability as a control variable. Findings indicate that a larger board size enhances oversight through diverse expertise, enabling stronger monitoring of managerial actions and reducing earnings manipulation. Board independence also supports transparency and accountability, aligning with Indonesia’s Financial Services Authority regulations. Moderated by Return on Assets (ROA), both board size and independence significantly impact real earnings management. Larger boards effectively limit manipulation in profitable firms, while high ROA strengthens the oversight of independent directors, further curbing manipulative practices. This combination of board characteristics and profitability contributes to a governance framework that supports ethical financial practices, aligned with agency theory to protect shareholder value and reduce agency costs. Future research could incorporate additional moderating variables, such as managerial leadership and dividend policy, or proxies from corporate governance indices, as well as explore board and gender diversity within board structure to further examine its influence on real earnings management.